P2_6 Surfin' Fury - Holesinsky, Tomas; Harrison, Zoe; Mandhai, Soheb; Harris, Ben G.S. (Physics Special Topics, 2016)
In a short film called Kung Fury, the main hero uses a person as a surfing board. We investigated the force he would need to push himself forward based on the kinetic friction and drag force. The force ranges between -335.24 ± 6.87 N and -980.74 ± 6.87 N.